RENAL RESISTIVE INDEX AND ARTERIAL STIFFNESS IN KIDNEY TRANSPLANTED PATIENTS - Pavleska-Kuzmanoska, Svetlana; Gjorgjievski, Nikola; Gerasimovska-Kitanovska, Biljana; Ristovska, Vesna; Stojceva-Taneva, Olivera; Ivanovski, Ninoslav (Journal of Morphological Sciences, 2019)
Measurement of renal resistive index is a non-invasive method used for assessment of microvascular lesions influenced by hemodynamic factors. The aim of our study was to introduce modern methods for assessing the arterial rigidity in patients with renal transplantation, which enable to treat and reduce it (arterial rigidity is potentially reversible), and thus reduce the risk of cardiovascular morbidity and mortality in this population. In a cross sectional study we assessed 28 kidney transplanted patients for pulse wave velocity, renal resistive index, ambulatory arterial stiffness index and pulse pressure. The data were statistically processed in a Statistica 7.1 for Windows. The average age of the participants was 44.07 years, 64.29% were men, average BW was 74.28 kg and BMI 25.29 kg/m 2 . The average graft duration was 82.28 months, and the average duration of hypertension was 142.89 months. Controlled hypertension was present in 35.71% of all hypertensive patients. Average pulse wave velocity was 6.64 ± 1.18 m/sec., ambulatory arterial stiffness index varied in the interval 0.36 ± 0.15 and the average renal resistive index of the graft’s main renal artery was 0.66 ± 0.08. Multiple regression analysis in the group of patients with graft duration below 7 years showed that both renal resistive index of the graft’s main renal artery and pulse wave velocity as dependent variables had significant and strong correlations with body weight and pulse pressure. Also, multiple regression analysis showed significant correlations between renal resistive index of graft’s main renal artery and pulse wave velocity as dependent or independent variables respectively. Our study showed that in the group of patients with graft duration less than a 7 years renal resistive index of the graft’s main renal artery and pulse wave velocity were significantly related but this was not confirmed in the group of patients with graft duration over 7 years. Thus suggests that we are not aware of all the factors that influence this relationship and more research studies are needed in that direction involving a larger number of respondents i.e. large prospective multicenter cohort studies with sufficient long follow-up period.